THE APPLICATION OF COGNITIVE-BEHAVIORAL COUNSELING USING SELF-RESTRUCTURING TECHNIQUES FOR STUDENTS WHO SPEAK IN PUBLIC AT STATE HIGH SCHOOL 12 IN EAST LUWU - Nurul Cahaya; Abdullah Sinring; Abdullah Pandang (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to examine the application of Cognitive Behavioral Counseling with Cognitive Restructuring Techniques in increasing students' confidence in public speaking at SMA Negeri 12 Luwu Timur. Specifically, this research sought to understand the overview of students' confidence before and after the intervention, as well as how the cognitive behavioral counseling with cognitive restructuring techniques was implemented. A quantitative approach with a Quasi-experimental design model and a nonequivalent control group design was used in this study. The research population consisted of 71 ninth-grade students, with a sample of 20 students divided into an experimental group and a control group, each comprising 10 students, selected through proportional random sampling. Data were collected using public speaking confidence scale instruments and observation guidelines, then analyzed using descriptive statistics and the Wilcoxon test. The research results indicate that at the pretest stage, the public speaking confidence level of students in both groups (experimental and control) was in the low category. However, after the intervention, the experimental group's confidence level showed a significant increase, reaching a very high category in the posttest, while the control group remained in the low category. The implementation of Cognitive Behavioral Counseling with Cognitive Restructuring Techniques was carried out through five structured stages: rational treatment, analysis of the counselee's thoughts, introduction and practice of coping thoughts (CT), shifting from negative thoughts to CT, and positive reinforcement and evaluation. Student participation during this process was recorded as high. The significant difference between the two groups indicates that the application of Cognitive Behavioral Counseling with Cognitive Restructuring Techniques is effective in increasing students' confidence in public speaking.